COMPLETION AND DISMISSAL OF CONVICTION LEGAL BASIS AND OBJECTIVE ASPECTS (World Bulletin of Management and Law, 2024)
Chapter 14, articles 78, 79 of the general part of the Criminal Code of the Republic of Uzbekistan are the legal bases of the provisions on criminal convictions, as well as the articles on "Completion of the criminal record" and "Removal of the criminal record". differences and the legal significance of conviction and its objective elements are highlighted. The issues of calculating terms are revealed and the statistical data of female and male representatives are introduced today
Keywords: Convicted men; Conviction; minors; removal